2015
DOI: 10.1093/rb/rbu019
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation resorbable polymer scaffolds with surface-precipitated calcium phosphate coatings

Abstract: Next-generation synthetic bone graft therapies will most likely be composed of resorbable polymers in combination with bioactive components. In this article, we continue our exploration of E1001(1k), a tyrosine-derived polycarbonate, as an orthopedic implant material. Specifically, we use E1001(1k), which is degradable, nontoxic, and osteoconductive, to fabricate porous bone regeneration scaffolds that were enhanced by two different types of calcium phosphate (CP) coatings: in one case, pure dicalcium phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
0
10
0
1
Order By: Relevance
“…Other contributing factors may be the polymer chemistry and pore structure. A series of studies in vitro and in the rabbit calvarial CSD model demonstrated that E1001(1k) has a high degree of bone biocompatibility and osteoconductivity [9,23,26]. These studies also described the bimodal pore structure of E1001(1k) scaffolds.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Other contributing factors may be the polymer chemistry and pore structure. A series of studies in vitro and in the rabbit calvarial CSD model demonstrated that E1001(1k) has a high degree of bone biocompatibility and osteoconductivity [9,23,26]. These studies also described the bimodal pore structure of E1001(1k) scaffolds.…”
Section: Discussionmentioning
confidence: 96%
“…After conducting a series of bone regeneration studies in the rabbit calvarial CSD model [9,24,26], we selected the goat calvarial model as a clinically relevant large animal model. Goats have metabolic and bone remodeling rates similar to those of humans [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this first study, we have been able to demonstrate how the early two steps in osteoclast activity, namely the formation of the “actin ring” and the formation of the “ruffled border”, can occur by using the CaP-free tyrosine-derived polycarbonate (E1001(1k)). E1001(1k) has shown promise in vivo where the polymer-bone interface exhibited morphological signs of integration and remodeling [ 15 , 16 ]. We investigated the ability of E1001(1k) to support osteoclast recruitment and activation in vitro , alone or in blends with RGD polypeptide, collagen type I and β-TCP (beta-tricalcium phosphate), factors involved in steps 1, 2 and 3 respectively.…”
Section: Introductionmentioning
confidence: 99%